PERAN MEDIA MASSA DALAM PENANGGULANGAN KEJAHATAN - Eka Nugraha Putra (University of Merdeka Malang, 2016)
In crime reduction policies, there are penal and non-penal.Where the penal nonpreventative.Efforts to nonpenal could be shaped anything, the role of mass media in forming the perception of crime and punishment is one.Themass media can do is through news the role of crime and have a partnership with law enforcement agencies.Butthere are still mass media that made the crime of a commodity course, while in conjunction with law enforcementagencies still limited to only as speakers course.The charge news in mass media particularly be caused by theviolence can make the impact fear and not educate people. Writing that is the outcome of research these writerslooked at how the role of media mass reduction policies evil, his involvement in law enforcement agencies and howto strengthen the role of mass media in reduction policies evil.There are several problems in construction mass mediawill the news crime like the use of terminology, the news balanced and the judge.This closely related to construction mass media will news evil, that then will run according to on function preventive.Mass media in the contextof policy penangggulangan evil may be also had a role in restore confidence the community and appreciation tolaw enforcement agencies, media a mass to be establish cooperation with law enforcement agencies.Do not have toa form of cooperation which are formil as long as can appreciate each other profession each and mutuallybeneficial. The role of media masses can also be implemented is all sides law enforcement agencies in constructionnews evil, until there is no law enforcement agencies whose performance be highlighted too big then cause a kindof competition with law enforcement agencies other.